WOMEN EMPOWERMENT IN VIJAY TENDULKAR’S DRAMA-KAMALA - G. Lalitha; Dr. V. Lizy (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Indian women have traditionally endured a range of difficulties, such as discrimination, abuse at home, marginalization, segregation, and gender inequality. Women's safety and security in public and private spheres are quite precarious today. This essay focuses on how the playwright uses drama to inspire women to follow in his footsteps and fundamentally transform society.